MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 19 KOTA BOGOR MELALUI PENGGUNAAN MEDIA SIMULASI VIRTUAL PhET PADA PELAJARAN IPA MATERI GETARAN - Wiwin Kurniawati (Journal of Social Studies Arts and Humanities (JSSAH), 2022)
IMPROVING LEARNING OUTCOMES OF GRADE 8 JUNIOR HIGH SCHOOL (SMP NEGERI 19 BOGOR) STUDENTS THROUGH THE USE OF PhET VIRTUAL SIMULATION MEDIA IN VIBRATION SUBJECT MATTER OF NATURAL SCIENCE LESSONSThe purpose of this study was to determine the increase in student learning outcomes regarding the subject matter of Vibration of Science in class VIII of SMP Negeri 19 Bogor City Even Semester of the 2021/2022 Academic Year through the use of PhET Virtual Simulation Media. The method used is a class action research method consisting of two cycles. In the first cycle, learning was carried out using the PhET Virtual Simulation Media, while in the second cycle, the enhanced PhET Virtual Simulation Media was used. In each cycle consists of four stages of research namely planning, implementation of action, observation, and reflection. The research data were analyzed using a comparative descriptive followed by reflection. Comparative descriptive is done by comparing the initial condition data, cycle 1 and cycle 2, both for learning outcomes. The results of this study indicate that: First, the use of PhET Virtual Simulation Media can improve student learning outcomes about Vibration material in science subjects in class VIII. It is proven that the percentage of student learning outcomes has increased from the initial condition the average daily test score was 68.91 in cycle I to 75.37 and in cycle II to 82.29 or in the final condition it increased by 19.42% from the initial condition. It is proven that the percentage of students' learning completeness increased from the initial condition of 61.11% in cycle I to 91.67% in cycle II or in the final condition it increased by 50.01% from the initial condition.